Point-of-care diagnostic tests for childhood urinary-tract infection: phase-contrast microscopy for bacteria, stick testing, and counting white blood cells. Issue 9 (6th September 2010) - Coulthard, Malcolm G; Nelson, Andrew; Smith, Terry; Perry, John D
Abstract : Aim: To evaluate point-of-care testing for childhood urinary-tract infections (UTI). Method: Point-of-care testing of prospectively collected sequential paired urines was compared with quantitative culture after serial dilution in 203 children, of whom 36 had UTIs. Proportionate reduction in uncertainty (PRU) plots were used to compare between methods and with published values. Results: Phase-contrast microscopy for bacteria, as with culturing a single urine and using a threshold of 10 5 bacteria/ml, was 100% sensitive, making it powerful to rule UTIs out. The specificity was slightly lower than urine culture (0.860 vs 0.925) except in girls >9 years where vaginal Lactobacillus contamination reduced it to 0.61, but this increased to 0.81 when 'urethral stream' urines were collected. Nitrite positivity is highly specific at 0.985, making it powerful at ruling UTIs in, but its low sensitivity (0.61) makes it unsafe to rule UTIs out. A PRU plot of 16 previous studies confirmed this. Though the presence of urinary white blood cells (WBC) correlates with UTI, whether tested by point-of-care of laboratory microscopy or by stick testing, the coefficient of determination is too low to make them clinically useful, alone or combined with nitrite analysis. Seventeen other studies confirmed this. Conclusion: Phase-contrast microscopy can rule out UTIs as reliably as urine culture but is immediate, which may be clinically important. To interpret positive results reliably, girls >9 years must collect a 'urethral stream' urine. While nitrite positivity is useful to rule UTIs in, negative results are unreliable. Urinary WBC testing has little value.